Impact of COVID-19 lockdown restrictions on cardiac rehabilitation participation and behaviours in the United Kingdom - Richard Kirwan; Fatima Perez de Heredia; Deaglan McCullough; Tom Butler; Ian G. Davies (BMC Sports Science, Medicine and Rehabilitation, 2022)
Abstract Background COVID-19 lockdown measures led to the suspension of centre-based cardiac rehabilitation (CR). We aimed to describe the impact of lockdown on CR behaviours and perceptions of efficacy in a sample of CR participants. Methods An online survey was conducted amongst CR participants from May to October 2020, COVID-19-related lockdown restrictions. Anthropometric data, participant-determined levels of motivation and self-perceived efficacy, CR practices etc., pre- and post-lockdown, were collected. Results The probability of practicing CR in public gyms and hospitals decreased 15-fold (47.2% pre-, 5.6% post-lockdown; OR[95% CI] 0.065[0.013; 0.318], p < 0.001), and 34-fold (47.2% pre, 2.8% post; OR[95% CI] 0.029[0.004; 0.223], p < 0.001), respectively. Amongst participants, 79.5% indicated that their CR goals had changed and were 78% less likely to engage in CR for socialization after lockdown (47.2% pre, 16.7% post; OR[95% CI] 0.220[0.087; 0.555]; p = 0.002). The probability of receiving in-person supervision decreased by 90% (94.4% pre, 16.7% post; OR[95% CI] 0.011[0.002; 0.056]), while participants were almost 7 times more likely to use online supervision (11.1% pre, 44.4% post; OR[95% CI] 6.824[2.450; 19.002]) (both p < 0.001). Fifty percent indicated that their enjoyment of CR was lower than before lockdown and 27.8% reported they would be less likely to continue with CR in the newer format. Conclusions Lockdown was associated with considerable changes in how CR was practiced, motivation levels and willingness to continue with CR. Further research is warranted to develop and improve strategies to implement in times when individuals cannot attend CR in person and not only during pandemics.